ПРОДВИЖЕНИЕ ПРАВ ЖЕНЩИН НА РАВНОЕ УЧАСТИЕ В ПОЛИТИЧЕСКОЙ ЖИЗНИ МОЛДОВЫ ЧЕРЕЗ ОБУЧЕНИЕ ЛИДЕРСТВУ - Боршевский, Андрей; Костаки, Георге (SUPREMANCE OF LAW, 2018)
The equality of women and men is one of the conditions for ensuring social justice, as well as the necessary and basic prerequisite for achieving equality, development and peace. And this equality cannot be achieved without the development of womens leadership, without the formation of women leaders. Leadership is the process of social influence, in which one person can enlist the help and support of other persons. This article became possible thanks to the support of the EU Delegation to Moldova in the framework of the Confi dence-building Measures Programme. The views and opinions expressed here are those of the authors and do not necessarily reflect the views of the EU Delegation to Moldova.
Keywords: Equal rights; leadership; leadership training; women; participation in public life.